1047. Global Surveillance: Susceptibility of Ceftolozane–Tazobactam Against Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa Isolates Collected From Bloodstream Infections in the United States From 2015 to 2017. (26th November 2018) - Arends, S J Ryan; Shortridge, Dee; Castanheira, Mariana; Streit, Jennifer M; Flamm, Robert K
Abstract: Background: Ceftolozane–tazobactam (C-T) is an antibacterial combination of a novel antipseudomonal cephalosporin and a β-lactamase inhibitor. C-T was approved by the US Food and Drug Administration in 2014 and by the European Medicines Agency in 2015 to treat complicated urinary tract infections, acute pyelonephritis, and complicated intra-abdominal infections. The Program to Assess Ceftolozane-Tazobactam Susceptibility (PACTS) monitors Gram-negative (GN) isolates resistant to C-T worldwide. In the current study, isolates were collected from patients hospitalized with bloodstream infections (BSIs) from 2015 to 2017 within the United States. Methods: A total of 3, 377 prevalence-based BSI GN isolates, including Escherichia coli (EC; 1, 422), Klebsiella pneumoniae (KPN, 630), and Pseudomonas aeruginosa (PSA; 344), were collected during 2015 to 2017 from 32 PACTS hospitals in the United States. Isolates were tested for C-T susceptibility by CLSI broth microdilution method in a central monitoring laboratory (JMI Laboratories). Other antibiotics tested were amikacin (AMK), cefepime (FEP), ceftazidime (CAZ), colistin (COL), levofloxacin (LVX), meropenem (MEM), and piperacillin–tazobactam (TZP). Antibiotic-resistant phenotypes analyzed (CLSI, 2018) for EC and KPN included carbapenem-R (CR) and non-CR extended-spectrum β-lactamase (ESBL); as well as CAZ-nonsusceptible (CAZ-NS), MEM-NS, and COL-NS PSA. Results: Of the 3, 377 BSI GN isolates, 3, 219 (95.3%) had a C-T MIC ≤ 4 mg/L. The three most prevalent GN species isolated from BSIs were EC (42.1%), KPN (18.7%), and PSA (10.2%). The %S of C-T and comparators for the top three pathogens are shown in the table. C-T showed activity against these isolates with %S of ≥96.0% against all three species. Of the comparators tested, AMK and COL also had high %S against these isolates. Conclusion: C-T demonstrated activity against the most prevalent contemporary GN isolates from BSIs in the US. C-T was the only beta-lactam that had ≥96%S against all three species: EC, KPN, and PSA. For PSA, C-T maintained activity (>90%S) against isolates resistant to CAZ, TZP, and MEM. These data suggest that C-T may be a useful treatment for GN BSI. Disclosures: S. J. R. Arends, Merck: Research Contractor, Research support. D. Shortridge, Merck: Research Contractor, Research support. M. Castanheira, Merck: Research Contractor, Research support. J. M. Streit, Merck: Research Contractor, Research support. R. K. Flamm, Merck: Research Contractor, Research support.